Recent Advances in the Synthesis of Di- and Trisubstituted Hydroxylamines - Jarvis Hill; Thomas D. Beckler; David Crich (Molecules, 2023)
As an underrepresented functional group in bioorganic and medicinal chemistry, the hydroxylamine unit has historically received little attention from the synthetic community. Recent developments, however, suggest that hydroxylamines may have broader applications such that a review covering recent developments in the synthesis of this functional group is timely. With this in mind, this review primarily covers developments in the past 15 years in the preparation of di- and trisubstituted hydroxylamines. The mechanism of the reactions and key features and shortcomings are discussed throughout the review.